Green Accounting Policy and Green Fiscal Policy on Regional Revenues in Supporting Sustainable Mangrove Ecosystems Mangrove Ecosystem Conservation in Jayapura, Papua - Otniel Safkaur; Aaron Asi Maruli Simanjuntak; Orpa Momot (Ilomata International Journal of Tax and Accounting, 2026)
The important issue of mangrove conservation is an element of sustainable development, presenting new opportunities for coastal protection, carbon sequestration, and sustainable improvement of community welfare. Green accounting and green fiscal policy influence regional revenue in mangrove conservation. This study uses a quantitative approach with panel data regression on 229 observations taken from regional regulations, budget realization, and development planning documents for the 2017–2025 period at the regional government level, which is still limited, especially in Papua and Jayapura. The results of the panel data regression study indicate that green accounting has a positive and significant impact on regional revenue. These findings demonstrate the relationship between public sector accounting and environmental policies for regional governments to design environmentally based fiscal policies. This study is designed to develop an empirical model integrating green accounting, green fiscal policy, regional revenue, and mangrove conservation in the context of the Papua/Jayapura regional government. Unlike previous studies that focused on the general environmental corporate sector, this study shows how accounting instruments and regional fiscal policies can support mangrove conservation and improve regional fiscal performance. These findings contribute to the literature on how the implementation of green accounting and regional revenue can improve transparency and mangrove forest rehabilitation. The integration of regional financial systems strengthens policy sustainability for stakeholders. This study has limitations in developing fiscal policies with measurable environmental benefits and coastal ecosystem sustainability. Overall, this study shows that successful mangrove forest conservation requires synergy between environmental accounting systems and regional fiscal commitments.